IDNLearn.com offers expert insights and community wisdom to answer your queries. Get accurate and detailed answers to your questions from our knowledgeable and dedicated community members.

Solve the quadratic equation by completing the square.

[tex]\[ 2x^2 + 12x = 66 \][/tex]

Fill in the values of [tex]\(a\)[/tex] and [tex]\(b\)[/tex] to complete the solutions.

[tex]\[
\begin{array}{l}
x = a - \sqrt{b} \\
x = a + \sqrt{b}
\end{array}
\][/tex]

(Note: Remove any unnecessary symbols and elements that were present in the original tabular formatting.)


Sagot :

To solve the quadratic equation [tex]\(2x^2 + 12x = 66\)[/tex] by completing the square, follow these step-by-step instructions:

1. Move the constant term to the left side:
[tex]\[ 2x^2 + 12x - 66 = 0 \][/tex]

2. Divide the entire equation by 2 to simplify:
[tex]\[ x^2 + 6x - 33 = 0 \][/tex]

3. Move the constant term back to the right side:
[tex]\[ x^2 + 6x = 33 \][/tex]

4. Complete the square:
To complete the square, we need to add [tex]\((\frac{b}{2})^2\)[/tex] to both sides, where [tex]\(b\)[/tex] is the coefficient of [tex]\(x\)[/tex]. Here, [tex]\(b = 6\)[/tex], so [tex]\((\frac{6}{2})^2 = 9\)[/tex].

Adding 9 to both sides:
[tex]\[ x^2 + 6x + 9 = 33 + 9 \][/tex]
[tex]\[ (x + 3)^2 = 42 \][/tex]

5. Take the square root of both sides:
[tex]\[ x + 3 = \pm\sqrt{42} \][/tex]

6. Solve for [tex]\(x\)[/tex]:
[tex]\[ x = -3 \pm \sqrt{42} \][/tex]

Thus, the solutions to the quadratic equation are:
[tex]\[ \begin{aligned} x &= -3 - \sqrt{42}, \\ x &= -3 + \sqrt{42}. \end{aligned} \][/tex]

Given the solutions are in the form [tex]\(x = a - \sqrt{b}\)[/tex] and [tex]\(x = a + \sqrt{b}\)[/tex],
we have:
[tex]\[ \begin{aligned} a &= -3, \\ b &= 42. \end{aligned} \][/tex]

Therefore, the values of [tex]\(a\)[/tex] and [tex]\(b\)[/tex] are:
[tex]\[ a = -3, \quad b = 42. \][/tex]